Lactiplantibacillus plantarum APsulloc 331261 (GTB1TM) attenuates depressive-like behavior and physiology via association with gut microbiota in BALB/c mice - Yuri Lee; Subin Yeo; Bobae Kim; Wilhelm H. Holzapfel; Hye-Ji Kang (Journal of Functional Foods, 2023)
As it has become clear that the gut microbiota play a critical role in brain function, probiotics have recently been spotlighted as therapeutic agents for various psychiatric disorders including major depressive disorder. Despite much interest, however, our understanding of the efficacy of probiotics for treating depression is still limited due to the complexity of the gut-brain axis. The present study aimed to evaluate the anti-depressive effect of Lactiplantibacillus plantarum APsulloc 331,261 in vivo and to elucidate the possible mechanism of action of this strain. The consumption of the strain APsulloc 331,261 could significantly reduce depressive-like behaviors and downregulate hippocampal inflammation. Interestingly, administration of the strain shifted the gut microbial community towards increasing acetate and propionate production. This modulation might stimulate increased serotonin synthesis in the colon and increase the serotonin level and neurogenesis in the brain. These results may serve to support the proposal of a new probiotic candidate strain for ameliorating depression.